Gaya Komunikasi Ketua Dewan Perwakilan Rakyat Kota (DPR-K) Subulussalam Dalam Menjalin Hubungan Dengan masyarakat - Indah Arihta Bintang; Bahrum Jamil; Armansyah Matondang (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2023)
The focus of the research is the communication style displayed by the Head of the Subulussalam Municipal People's Representative Council (DPR-K) in establishing relationships with the people of Subulussalam City. This research was conducted in the City of Subulussalam. Data collection was carried out by means of observation, direct interviews and documentation related to research. As for the resource persons in this study, namely the key informants, the researchers chose the people of Subulussalam City, while those who became additional informants were the Chair of the DPR-K, the Secretary of the Council and Public Relations of the DPR-K Subulussalam. To get valid information in accordance with the author's research needs. The results of the research interview on the communication style presented by the Chairperson of the DPR-K Subulussalam dominate the Equalitarian style and structural style communication styles. This communication is considered effective because it is able to make it easier for the public to receive good information from the Chairperson of the DPR-K Subulussalam. It's just that the communication style possessed by the chairman of the DPR-K Subulussalam as a leader has not been found in all employees or fellow members in the DPR-K Subulussalam office so communication with the community is not very good.